Drosophila Miro is required for both anterograde and retrograde axonal mitochondrial transport. - Russo, G.J.; Louie, K.; Wellington, A.; Macleod, G.T.; Hu, F.; Panchumarthi, S.; Zinsmaier, K.E. (Journal of Neuroscience, 2009)
Microtubule-based transport of mitochondria into dendrites and axons is vital for sustaining neuronal function. Transport along microtubule tracks proceeds in a series of plus and minus end-directed movements that are facilitated by kinesin and dynein motors. How the opposing movements are controlled to achieve effective transport over large distances remains unclear. Previous studies showed that the conserved mitochondrial GTPase Miro is required for mitochondrial transport into axons and dendrites and serves as a Ca(2+) sensor that controls mitochondrial mobility. To directly examine Miro's significance for kinesin- and/or dynein-mediated mitochondrial motility, we live-imaged movements of GFP-tagged mitochondria in larval Drosophila motor axons upon genetic manipulations of Miro. Loss of Drosophila Miro (dMiro) reduced the effectiveness of both anterograde and retrograde mitochondrial transport by selectively impairing kinesin- or dynein-mediated movements, depending on the direction of net transport. Net anterogradely transported mitochondria exhibited reduced kinesin- but normal dynein-mediated movements. Net retrogradely transported mitochondria exhibited much shorter dynein-mediated movements, whereas kinesin-mediated movements were minimally affected. In both cases, the duration of short stationary phases increased proportionally. Overexpression (OE) of dMiro also impaired the effectiveness of mitochondrial transport. Finally, loss and OE of dMiro altered the length of mitochondria in axons through a mechanistically separate pathway. We suggest that dMiro promotes effective antero- and retrograde mitochondrial transport by extending the processivity of kinesin and dynein motors according to a mitochondrion's programmed direction of transport.